2016
DOI: 10.1177/1078155215612541
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a pharmacist-led oral chemotherapy-monitoring program in patients with metastatic castrate-resistant prostate cancer

Abstract: These results suggest a potential opportunity exists to maximize oral chemotherapy treatment outcomes with the addition of a formalized monitoring program directed by an oncology pharmacist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(102 citation statements)
references
References 14 publications
(25 reference statements)
3
91
0
Order By: Relevance
“…Moreover, two studies reported a significant increase in medication adherence. All studies that measured other process indicators reported a significant improvement in knowledge‐attitude‐practice for chemotherapy, awareness and knowledge regarding blood pressure management and adherence to laboratory parameter monitoring following pharmacist interventions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, two studies reported a significant increase in medication adherence. All studies that measured other process indicators reported a significant improvement in knowledge‐attitude‐practice for chemotherapy, awareness and knowledge regarding blood pressure management and adherence to laboratory parameter monitoring following pharmacist interventions.…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the titles and abstracts, 617 records were excluded because they did not include a study of pharmacist interventions in adult patients with cancer; did not assess the impact of interventions; or included non‐ambulatory patients. The remaining 40 records were selected for full‐text examination, of which 11 met all the eligibility criteria and were included in this systematic review . The excluded studies and the reasons for their exclusion are detailed in Appendix 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations